Testing for double inflation with WMAP - Parkinson, David; Amendola, Luca (Physical review. D, Particles, fields, gravitation, and cosmology, 2005)
With the WMAP data we can now begin to test realistic models of inflation involving multiple scalar fields. These naturally lead to correlated adiabatic and isocurvature (entropy) perturbations with a running spectral index. We present the first full (9 parameter) likelihood analysis of double inflation with WMAP data and find that despite the extra freedom, supersymmetric hybrid potentials are strongly constrained with less than 7% correlated isocurvature component allowed when standard priors are imposed on the cosomological parameters. As a result we also find that Akaike and Bayesian model selection criteria rather strongly prefer single-field inflation, just as equivalent analysis prefers a cosmological constant over dynamical dark energy in the late universe. It appears that simplicity is the best guide to our universe.